THU0079 Fatigue in rheumatoid arthritis patients: The impact of disease activity, pain, disability and depressive disorders. (23rd January 2014) - Lisitsyna, T.A.; Seravina, O.; Kovalevskaya, O.; Veltishchev, D.; Zeltyn, A.; Novikova, D.; Popkova, T.; Novikov, A.; Alexandrova, E.; Nasonov, E.
Abstract : Background: evidence exists that fatigue is a significant problem for rheumatoid arthritis (RA) patients (pts). The causes of fatigue aren't enough investigated. Chronic pain syndrome, depression and disability are confounding fatigue factors. Altered or increased cytokines production is a possible biological explanation of fatigue. Objectives: to determine the prevalence of fatigue in RA-pts and it's associations with some disease features. Methods: 125 RA-pts were enrolled in this study. All of them met the full ACR criteria for RA classification. 86% RA-pts were women with a median age of 50 yrs (41; 54). The disease activity was assessed by DAS28 score. 52% of RA-pts had a high activity of disease (DAS28>5, 1). 67% RA-pts were taking prednisone in median dose 5 mg/day (0; 10). 79% RA-pts were taking DMARDs. Psychiatric disorders were diagnosed in accordance with the ICD-10. Psychiatric scales used: Hospital Anxiety and Depression Scale (HADS), Hamilton Anxiety Rating Scale, Perceived Stress Scale (PSS-10). Anxiety-depressive disorders were detected in 85% RA-pts: depressive episodes and dysthymia prevailed (37% and 33% accordingly). Fatigue was evaluated using Fatigue Severity Scale (FSS).The Brief Pain Inventory (BPI) was used for pain assessment. Heart rate variability (HRV) was analyzed, using 24-hour Holter electrocardiographic data. Risk of cardiovascular diseases (CVR) was assessed by Framingham 10-year scale. Quality of life (QoL) was evaluated using EQ-5D scale. Results: 79% RA-pts had clinically relevant fatigue (>4). The presence of fatigue didn't depend on age, duration of disease, DAS28 score, radiological RA stage, hsCRP, RF-IgM, anti-CCP, hemoglobin and ESR levels, use of prednisone. But there are significant difference were found in number of RA-pts with depressive episodes, sleep disturbances, high stress level in pts with vs without fatigue (p<0, 01). RA-pts with fatigue had more tender and swollen joint counts (p<0, 01), high degree (II-IV) of functional disability (p=0, 042), high TNF-α level (p<0, 05), more often had osteoporosis (p=0, 03), low HRV (pNN50%) (p=0, 034) and high CVR (p=0, 009). RA-pts with fatigue less often (76 vs 90%, p=0, 07) used DMARDs and pain had more influence for mood, sleep, ability to work in these RA-pts. Severity of fatigue was negative correlated with QoL (R=-0, 45, p=0, 001) and positive correlated with HADS-level of depression (R=0, 48, p<0, 0001), interleikine-1β (R=0, 36, p=0, 023) and BPI-max levels (R=0, 31, p=0, 004). Conclusions: the results demonstrated high prevalence of fatigue in surveyed RA-pts. Fatigue is complex condition which is more associated with high stress level, depressive disorders, some disease activity signs (swollen and tender joints), pain, functional disability and has a negative impact on QoL. Increased pro-inflammatory cytokines production is a possible biological explanation of fatigue. Disclosure of Interest: None Declared